Aflatoxin M1 and ochratoxin A in baby formulae marketed in Lebanon: Occurrence and safety evaluation. (December 2019) - Elaridi, Jomana; Dimassi, Hani; Hassan, Hussein
Abstract: Aflatoxin M1 (AFM1) and ochratoxin A (OTA) are hepatotoxin and nephrotoxin mycotoxins, respectively. An investigation on their presence in baby formulae marketed in Lebanon was conducted. Infant formula samples were collected from 42 brands over two production dates (n = 84) during 2017–2018 and analyzed for AFM1 and OTA using competitive-enzyme-linked immunosorbent assay. Mean (±standard deviation) of AFM1 and OTA concentrations were determined to be 20.1 ± 1.3 ng/kg and 0.37 ± 0.10 μg/kg, respectively. In terms of AFM1, level of contamination ranged between not detected and 48.1 ng/L; 13 (31%) brands had an average level above the European Commission (EC) limit. With respect to OTA, contamination level ranged between not detected and 0.96 μg/kg; 14 (33%) brands had an average level above the EC limit. Five (12%) brands had both AFM1 and OTA levels above EC limits. Differences in the contamination level in each brand vs. average of all others, between production dates, and between seasons were assessed. There was a significant (p < 0.05) difference in AFM1 and OTA levels among 37 (88%) and 14 (33%) brands, respectively, compared to the average of all others. There was a significant (p < 0.05) difference between production dates for AFM1, but not for OTA. No significant (p < 0.05) difference was found between fall/winter and spring/summer for both mycotoxins. This study is the first-of-its-kind concerning the safety assessment of infant formulas regarding mycotoxins in Lebanon. Highlights: Mean (±SD) of AFM1 and OTA concentrations were determined to be 20.1 ± 1.3 ng/kg and 0.37 ± 0.10 μg/kg, respectively. In terms of AFM1, 13 (31%) brands had an average level above the European Commission (EC) limit (25 ng/kg). With respect to OTA, 14 (33%) brands had an average level above the EC limit (0.5 μg/kg). Five (12%) brands had both AFM1 and OTA levels above EC limits. No significant (p < 0.05) difference was found between fall/winter and spring/summer for both AFM1 and OTA.